A lesion extending three or more slices as a predictor of progressive infarction in anterior circulation small subcortical infarction - Lin, Jing; Mao, Xiaocheng; Liao, Yunfang; Luo, Si; Huang, Qin; Song, Ziwei; Li, Shumeng; Li, Chengjin; Qiu, Yuexin; Wu, Yuhang; Zhu, Min; Li, Xiaobing; et al. (Frontiers in Neurology, 2022)
Progressive infarction (PI) is common in small subcortical infarction and may lead to a poor outcome. The purpose of our study is to identify neuroimaging predictors for PI. From April 2017 to December 2020, we enrolled 86 patients with an anterior circulation subcortical infarction within 48 h after onset. Progressive infarction was defined by an increase of ≥ one point in motor power or ≥ two points in the total National Institute of Health Stroke Scale score within 7 days after admission and further confirmed by diffusion-weighted imaging (DWI). To identify predictors, demographic characteristics, clinical information, laboratory date, and neuroimaging characteristics were evaluated. The infarct size and infarct slice number were measured by DWI. We found that thirty-one patients (36%) had PI. In a univariate analysis, the patients with PI had higher levels of triglyceride, lower levels of blood urea nitrogen and prothrombin time, and a higher frequency of infarct slice number ≥ three compared to the patients without PI. After logistic regression stepwise adjustment for all considered relevant confounders, infarct slice number ≥ three slices proved to be independently associated with PI (OR = 4.781, 95% CI 1.677–13.627; OR = 4.867, 95% CI 1.6–14.864; OR = 3.584, 95% CI 1.034–12.420). Our study showed that a lesion extending ≥ three slices on DWI is an independent predictor for progressive infarction in patients with anterior circulation small subcortical infarction.